Aristotle's Phronimos Should Also Turn the Other Cheek - Stackle, Erin (Philosophy & theology, 2017)
Preliminary assessment of Aristotle’s treatment of justice suggests that he would consider unjust Jesus’s injunction to turn your other cheek to one who has unjustly struck you. Further consideration, however, shows that obeying such an injunction would qualify, even by Aristotle’s criteria, as a more just response than reciprocating the blow. Turning one’s cheek provides the assailant an opportunity to make a choice that could improve his character, which improvement is crucial to the political good that is the primary concern of justice in the full sense. Remaining concerns about rectification are obviated by considering how the megalopsukhos navigates honor.